Museum-based programs for socially isolated older adults: Understanding what works. (November 2017) - Todd, Carolyn; Camic, Paul M.; Lockyer, Bridget; Thomson, Linda J.M.; Chatterjee, Helen J.
Abstract: This paper presents research findings that help to understand how museum programs created opportunities to enhance wellbeing and health, and changed experiences of social isolation in older adults. The research conceptualized how program elements enabled both individual experiences and relational processes to occur. These components operated within a context that was enriched by the museum as a place to support wellbeing and enhance social interaction. To meaningfully support socially isolated older people as part of local public health strategies, museums need to be accessible and engaging places that purposively support social interaction by involving people and objects, participating in multiple sessions over time, that are facilitated by skilled and knowledgeable staff. Highlights: Social isolation is an increasing problem for many adults over 65 years old. Museums, as public places, offer accessible social and learning opportunities. As part of public health initiatives, museum-based programs can help reduce isolation and loneliness.